Servidor para autenticación en la red de comunicación de datos del GAD municipal del cantón Bolívar - Pazmiño Palma, María Gabriela (2016)
This study aimed to implement an authentication method that restricts access to unauthorized wireless and wired network GAD Municipal Bolívar Canton users, allowing strengthen and improve the performance of the intranet, existing resources were organized and controlling flow authenticated information for each computer and smartphone. pfSense operating system and the installation packages FreeRADIUS, Squid and SquidGuard were necessary to manage LAN services. The methodology used is PPDIOO that is proposed by Cisco, providing a focus on the development, design and implementation of networks. The main result shows that to properly manage resources based on priorities and constraints navigation is achieved to improve the availability of internet access and avoid congestion.